Problems in Mathematics Learning Multiple Materials Viewed From Low-Grade Students' Learning Interest Aspect - Maya Marini; Ahmad Ilham Asmaryadi; Ratnawati Ratnawati (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2022)
This research is motivated by a lack of understanding in learning mathematics multiplication material. This study aims to describe the problems in learning mathematics with multiplication material in terms of the learning interest of low-grade students at SDN 13 Sitiung Dharmasraya. This researcher uses qualitative descriptive research. The research subjects were homeroom teacher for grade 2, homeroom for grade 3, and grade 4 for low-grade students. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique in this study uses the Milles and Huberman model which consists of data collection, data reduction, data presentation, and conclusion drawing/verification. The results showed that the problems in learning mathematics multiplication material can be seen from several factors, one of which is the student's interest in learning, which can be seen from the indicators of student interest in learning, namely, students' feelings of pleasure, attention in learning, lesson materials and teacher attitudes. interesting, the benefits and functions of the subjects. From this, it can increase students' interest in learning mathematics in multiplication material.